Work Analysis of Compliant Leg Mechanisms for Bipedal Walking Robots. (24th September 2013) - Kim, Byoung-Ho
In this study, we analyse the work of bipedal walking robots with compliant feet. For this purpose, a walking model of bipedal robots with compliant feet is considered. The ligamentous structure of the human foot is used for the compliant feet mechanisms of the bipedal robot considered herein. A work principle is used for determining the corresponding work at the joint space of the compliant legs according to the reaction force which is propagated from the foot space. The usefulness of the work analysis is demonstrated through exemplary simulations. Consequently, it is shown that the work analysis can be used for evaluating the fatigue of the bipedal robot accumulated by the physical walking impact between the supporting foot and the contact surface. Furthermore, comfortable walking by means of footgear with a compliance is addressed.